Whistlin' Dixie in a nor'easter [large type] - Patton, Lisa (Thorndike Press large print core, 2010)
It was only because Leelee Satterfield had adored her husband since the tenth grade that she agreed to leave Memphis to follow his dream of managing an inn in Vermont. But when Leelee is left swindled and snowbound, she's forced to confront the true depth of her Southern grit in this foreign town. Readers will rejoice in the hilarious antics, colorful cast of characters, and heartfelt moments in Whistlin' Dixie in a Nor'easter.